The development, implementation and evaluation of a training intervention for primary health care providers on brief behaviour change counselling, and assessment of the provider’s competency in delivering this counselling intervention - Malan, Johanna Elizabeth (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.